PENGARUH KETERLIBATAN PENGGUNA DAN UKURAN ORGANISASI PADA EFEKTIVITAS PENGGUNAAN SISTEM INFOMASI AKUNTANSI - Kharisma, Made Dwinda; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
This study aims to determine whether the personal capabilities of information systems can moderate the influence of user involvement and organizational size on the effectiveness of the use of accounting information systems . This study used sampling methods done by purposive sampling approach and obtained 66 samples . This research was conducted at PT Bank Sinar Harapan Bali Denpasar . The results of this study indicate that user involvement had no effecton the effectiveness of the use of accounting information systems , while the size ofthe organization affect the effectiveness of the use of accounting information systems . Personal capabilities of information systems can only moderate the effect of organizational size on the effectiveness of the use of accounting information systems .
Keywords: effectiveness of the use of AIS, user involvement, size of organization, personnel information system capabilities